Control of surface plasmon localization via self-assembly of silver nanoparticles along silver nanowires - Tran, M Linh; Centeno, Silvia P; Hutchison, James A; Engelkamp, Hans; Liang, Duoduo; Van Tendeloo, Gustaaf; Sels, Bert F; Hofkens, Johan; Uji-i, Hiroshi (Journal of the American Chemical Society, 2008)
A simple and low-cost method to create metal-metal hybrid nanostructures possessing fairly regularly spaced "hot-spots" of surface plasmon resonances is proposed. The nanohybrid structure was prepared via self-assembly during a simple drop-casting procedure, using chemically synthesized silver nanowires and silver nanoparticles prepared in a single batch of a polyol process. Wide field illumination of these nanohybrids produced hot-spots with spacings of around 500 nm to 1 microm. The intensity of the emission/scattering from the hot-spots fluctuates over time. The proposed structure can be useful for the development of molecular-sensors or as a substrate for surface enhanced Raman/fluorescence spectroscopy.